Natural Food Intake and Its Contribution to Tambaqui Growth in Fertilized and Unfertilized Ponds - Lima, Adriana Ferreira [UNESP]; dos Reis, Anderson Guilherme Pereira; Costa, Vladimir Eliodoro [UNESP]; Valenti, Wagner Cotroni [UNESP] (MDPI, 2024)
Natural food available in ponds can complement formulated feed in fed aquaculture. This study elucidated the natural food intake and its contribution to tambaqui (Colossoma macropomum) growth in fertilized and unfertilized ponds, using stable isotope and stomach contents analyses. Additionally, it described the impact of fertilization management on natural food availability, fish performance, and production costs. Tambaqui juveniles (93.8 ± 15.0 g) were stocked (0.55 fish/m2) in fertilized (Fert) and unfertilized (NoFert) ponds (600 m2) for a culture period of 10 months in quadruplicate. A lower food conversion ratio was observed in Fert ponds. The main natural food items ingested by tambaqui were insects, vegetables, and cladocerans. Plankton contributed 39.4% and 10.7% of muscle formation in Fert and NoFert ponds, respectively. Pond fertilization (2.45 g of nitrogen and 0.80 g of phosphorus per square meter every two weeks) did not significantly affect fish growth, survival, or productivity but had a slightly influence on water quality parameters. However, fertilization increased the zooplankton density (through phytoplankton) in the water, thereby increasing autochthonous food availability for tambaqui consumption. This species demonstrates the ability to alternate between natural food sources and commercial feed without compromising its development. Consequently, tambaqui exhibits suitability for farming within restorative and integrated aquaculture systems as well as intensive systems reliant on commercial feed.
Keywords: Colossoma; cost-effectiveness; plankton; pond fertilization; pond natural food; stable isotope; trophic ecology